Sol-gel processing of a covalent organic framework for the generation of hierarchically porous monolithic adsorbents - Carrington, ME; Rampal, N; Madden, DG; O’Nolan, D; Casati, NPM; Divitini, G; Martín-Illán, JÁ; Tricarico, M; Cepitis, R; Çamur, C; Curtin, T; Silvestre-Albero, J; et al. (Cell Press, 2022)
Covalent organic frameworks (COFs) have emerged as a versatile material platform for such applications as chemical separations, chemical reaction engineering, and energy storage. Their inherently low mechanical stability, however, frequently renders existing methods of pelletization ineffective, contributing to pore collapse, pore blockage, or insufficient densification of crystallites. Here, we present a process for the shaping and densifying of COFs into robust centimeter-scale porous monoliths without the need for templates, additives, or binders. This process minimizes mechanical damage from shear-induced plastic deformation and further provides a network of interparticle mesopores that we exploit in accessing analyte capacities above those achievable from the intrinsic COF structure. Using a lattice-gas model, we accurately capture the monolithic structure across the mesoporous range and tie pore architecture to performance in both gas-storage and -separation applications. Collectively, these results represent a substantial step in the practical applicability of COFs and other mechanically weak porous materials.